Debate-theater: A modality of spontaneous theater - da Silva Freitas, Andreia (2020)
This text aims to present the potential of the Spontaneous Theater modality, named Debate-Theatre (T-D), developed by the psychodramatist Moysés C. de Aguiar Netto and other professionals of the time, applied and diffused by the Companhia do Teatro Espontâneo, also created by the author in Brazil. Thus, perspectives on the Spontaneous Theater and the Debate-Theatre are discussed here and then a brief report of the experience of a Debate-Theatre carried out in the educational space is presented with a mostly non-psychodramatist audience.